Supplement to the Collatz Conjecture - Nikolaychuk, Anatoliy (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
For any natural number was created the supplement sequence, that is convergent together with the original sequence. The parameter - index was defined, that is the same tor both sequences. This new method provides the following results: All natural numbers were distributed into different classes according to the corresponding indexes; The analytic formulas ( not by computer performed routine calculations) were produced, the formulas for groups of consecutive natural numbers of different lengths, having the same index; The new algorithm to find index for any natural number was constructed and proved.